2010
DOI: 10.1007/s10895-010-0688-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aluminum Ion with Morin in a Medium Comprised by Ionic Liquid–Water Mixtures

Abstract: In this study we have employed two ionic liquids (ILs) as a new media for the analysis of aluminum in aqueous solutions by spectrofluorimetric method. ILs are liquid salts and they have no measurable vapor pressure up to their thermal decomposition point, >300 °C. This lack of vapor pressure makes these materials highly attractive for many studies as they can be used as clean solvents. Besides they are promising environments for analysis purposes and optical sensor designs. The results revealed that absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…17 There are also some studies indicating that ILs may constitute a new class of surfactants with special properties resulting in considerable enhancements in analytical response. 18,19 In recent years, it has also been shown that ILs supplied a stable and sensitive environment in some analytical applications. 20−22 There are increasing numbers of studies on the preconcentration or selective extraction of metal ions using ILs.…”
Section: Tolu D Ne Bluementioning
confidence: 99%
“…17 There are also some studies indicating that ILs may constitute a new class of surfactants with special properties resulting in considerable enhancements in analytical response. 18,19 In recent years, it has also been shown that ILs supplied a stable and sensitive environment in some analytical applications. 20−22 There are increasing numbers of studies on the preconcentration or selective extraction of metal ions using ILs.…”
Section: Tolu D Ne Bluementioning
confidence: 99%
“…[6][7][8] Due to both negative and positive aspects of aluminum, it is very important to develop analytical methods for the determination of aluminum at trace levels both in environmental and biological samples. 9,10 Analytical methods which are widely used for the determination of aluminum are chemiluminescence analysis, 11 electrothermal atomic absorption spectrometry (ETAAS), 12 inductively coupled plasma optical emission spectrometry (ICP-OES), 13 electroanalytical techniques 14 and high performance liquid chromatography (HPLC). 15 However, due to a lack of selectivity and sensitivity and interference effects of the matrix, the direct determination of Al(III) using these methods are not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable attention has been focused on the development of selective and sensitive optical sensors that can detect biologically important ions by color and fluorescence responses. [26][27][28][29] Several fluorescent probes based on naphthalene, [30][31][32][33][34][35] tetrazole, 36 morin, 37,38 8-hydroxyquinoline, [39][40][41] coumarin 19,42,43 BODIPY 44 and Schiff base 45 have been designed and synthesized for determination of Al 3+ . Recently, rhodamine derivatives have been proven to be an ideal model to construct fluorescent probes because they possess excellent spectroscopic properties such as high fluorescence quantum yield, visible light excitation as well as long wavelength emission.…”
Section: Introductionmentioning
confidence: 99%